Women's appraisal, interpretation and help-seeking for possible symptoms of breast and cervical cancer in South Africa: a qualitative study - Jane Harries; Suzanne E. Scott; Fiona M. Walter; Amos D. Mwaka; Jennifer Moodley (BMC, 2020)
Abstract Background In South Africa, breast cancer is the most commonly diagnosed cancer and cervical cancer the leading cause of cancer mortality. Most cancers are diagnosed at a late-stage and following symptomatic presentation. The overall purpose of the study was to inform interventions aimed at improving timely diagnosis of breast and cervical cancer. Methods In-depth interviews were conducted with women with potential breast or cervical cancer symptoms from urban and rural South Africa. Participants were recruited from a community-based cross-sectional study on breast and cervical cancer awareness. Data were analysed using a thematic analysis approach. Results Eighteen women were interviewed (10 urban, 8 rural): the median age was 34.5 years (range 22-58). Most were unemployed, and five were HIV positive. Themes included impact and attribution of bodily changes; influence of social networks and health messaging in help-seeking; management of symptoms and help-seeking barriers. Breast changes were often attributed to manual activities or possible cancer. Women were often unsure how to interpret vaginal symptoms, attributing them to HIV, hormonal contraceptives, or partner infidelity. Concerns about cancer were based on health information from the radio, social networks, or from primary care providers. Prompt care seeking was triggered by impact of symptoms on personal lives. Rural women, especially with possible symptoms of cervical cancer, experienced challenges during help-seeking including judgmental attitudes of clinic staff. Most participants were skeptical of traditional medicine. Conclusions This is the first study exploring interpretation of possible breast and cervical cancer symptoms at a community level in South Africa. The process of interpreting bodily changes, symptom attribution and help-seeking is complex and influenced by women's everyday life experiences. Timely diagnosis interventions should not only include cancer symptom awareness but also address individual, structural and health systems related barriers to care.